(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Parkinson’s disease is a progressive neurodegenerative disorder characterized by the degeneration of dopaminergic neurons and the accumulation of α-synuclein protein aggregates in the brain. It leads to a variety of motor symptoms, including tremor, rigidity, bradykinesia, and postural instability, as well as numerous non-motor manifestations. Pharmacological therapy, particularly treatment with levodopa, remains the main approach for symptomatic control; however, long-term drug therapy is frequently associated with the development of motor fluctuations and dyskinesia, which significantly complicate disease management in advanced stages. In recent decades, deep brain stimulation has emerged as one of the most important neurosurgical approaches for the treatment of advanced Parkinson’s disease in patients whose symptoms cannot be adequately controlled with pharmacological therapy alone. This technique involves the delivery of controlled electrical impulses to specific brain structures, most commonly the subthalamic nucleus, in order to modulate abnormal neural activity within the basal ganglia–thalamocortical motor circuits. By altering pathological patterns of neuronal firing, deep brain stimulation can restore more physiologically organized neural signaling within motor pathways. Clinical studies have demonstrated that deep brain stimulation significantly improves motor function, reduces motor complications, increases “on” time without troublesome dyskinesia, and enhances patients’ quality of life. Long-term follow-up investigations also show sustained therapeutic effects together with a reduction in antiparkinsonian medication requirements. The present article examines the epidemiology and pathophysiology of Parkinson’s disease in the context of abnormal neuronal electrical activity and analyzes the application of deep brain stimulation as a modern neurosurgical method that utilizes electrical impulses to modulate pathological brain circuits in the treatment of Parkinson’s disease.